Efficiency Analysis of Organic Farming Systems - A Review of Concepts, Topics, Results and Conclusions - Sebastian Lakner; Gunnar Breustedt (German Journal of Agricultural Economics (GJAE), 2017)
This article summarizes the literature on efficiency and productivity of organic farming. We distinguish between studies that concentrate on specific problems of the organic sector and studies that compare conventional and organic farms. Organic farms can on average improve their efficiency by 21%-points (SFA) and 27%-points (DEA). In comparing efficiency and productivity of organic with
Keywords: 330